The Measurement of The Three Components of The Cutting Force During The Turning Process - Nemes, Csaba; Javorek, Lubomir; Bodzás, Sándor; Pálinkás, Sándor (International Journal of Engineering and Management Sciences, 2019)
We carried out the measurement of the three components of the cutting force as a function of the modification of the depth of cut during the longitudinal turning process. The results show that if we increase the depth of cut, all three components of the cutting force shows increasing tendency, regardless of how much the cutting speed and feed speed were performed during the measurements [1] [2] [3] [4].